Strategi Pembelajaran Diferensiasi Berbasis Teknologi untuk Mengatasi Learning Loss pada Siswa Sekolah Dasar Pascapandemi - Vina Pariska; Lili Herawati; Ayu Kurniasih (PGSD UNU NTB, 2025)
This study aims to analyze the effectiveness of technology-based differentiated learning strategies in addressing learning loss among elementary school students in the post-pandemic period. Educational disruptions during the pandemic led to declines in academic skills, motivation, and student engagement. This strategy offers a personalized and adaptive approach by utilizing digital platforms, interactive applications, and adaptive technologies to tailor learning materials to individual needs. The study employs a mixed-methods approach, combining quantitative data from academic competency tests and qualitative data from classroom observations and interviews with teachers and students. The results show significant improvements in reading, writing, and numeracy skills, as well as increased student motivation, engagement, and self-confidence. The implementation of this strategy enables project-based learning, STEM-STEAM approaches, and real-time formative assessment, allowing for more targeted interventions. This strategy also supports inclusivity for students with special needs and enhances psychological well-being. Its successful implementation is influenced by school support, teacher readiness, parental involvement, and the effective use of technology. The findings confirm that this strategy is effective, adaptive, and inclusive in accelerating the recovery of learning loss in elementary schools in a sustainable manner.